2022
DOI: 10.3390/photonics9030135
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a New Trifocal Diffractive Corneal Inlay for Presbyopia Correction Using an Adaptive Optics Visual Simulator

Abstract: In this work, we analyze a proposal of a new intracorneal diffractive lens for presbyopia correction that could allow good, distance, intermediate and near vision. By using an adaptive optics visual simulator, we study the influence of two factors in the inlay performance: the spherical aberration (SA) and the potential errors of in thickness, induced in the manufacturing process. We show that the inlay through-the-focus imaging performance can be customized with the SA value, favoring either distance–intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Instead of working with actual patients, we employed an artificial eye with a power of 20 D, which consisted of an achromatic doublet (AC254-050-A-ML, Thorlabs Inc., Newton, NJ, USA) equipped with a CMOS sensor (EO-10012C LE, 8 bits, 3840 × 2748 pixels, 6.41 × 4.59 mm) as previously described in other works. This approach has been utilized to assess different MIOL designs and corneal inlays [24,28,29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of working with actual patients, we employed an artificial eye with a power of 20 D, which consisted of an achromatic doublet (AC254-050-A-ML, Thorlabs Inc., Newton, NJ, USA) equipped with a CMOS sensor (EO-10012C LE, 8 bits, 3840 × 2748 pixels, 6.41 × 4.59 mm) as previously described in other works. This approach has been utilized to assess different MIOL designs and corneal inlays [24,28,29].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in this work, the aim is to study the influence of different positive and negative SA values (which arise as a result of refractive surgeries) on the optical performance of the FEMTIS Comfort IOL. To this end, we employed a commercial adaptive optics visual simulator to obtain the through-focus modulation transfer function (TF-MTF) and images of a tumbling E optotype for different object vergences [24]. Since IOLs are typically designed for eyes with a standard corneal geometry and aberrations, it is important to investigate their performance under varying degrees of aberrations in the eye.…”
Section: Introductionmentioning
confidence: 99%
“…They found that spherical aberration extends the focal depth of the intermediate focus which may allow for customized focal distribution that fits the needs of each patient. 46 …”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue gathers contributions in these fields that emphasize eye care. A total of 12 articles are published in this issue, demonstrating the extraordinary progress in a variety of scenarios, from ocular image processing and artificial intelligence [1][2][3][4] to ocular lens design and characterization [5][6][7][8], and visual performance [9][10][11][12]. Half of the articles deal with ocular lens implants, which has been revealed to be a very active field in surgery [5][6][7]9,11,12].…”
mentioning
confidence: 99%
“…Their optimization method allows a parameter-free iterative approach to be performed that yields the best trade-off between extending the depth of focus and achieving the best image quality. Martinez-Espert et al [5] proposed a new intracorneal diffractive lens for presbyopia correction that could allow reasonable distance, intermediate, and near vision. They used an adaptive optics visual simulator to study the influence of spherical aberration and the potential errors in thickness caused during the manufacturing process.…”
mentioning
confidence: 99%